UPAYA PENINGKATAN EFEKTIVITAS KERJA KANTOR CAMAT SIBOLGA SAMBAS DITINJAU DARI PELAKSANAAN KEGIATAN DIKLAT (PENDIDIKAN DAN PELATIHAN) - Koto, Mhd. Shafwan; Rani Saragih, Laila Gusti (Akrab Juara : Jurnal Ilmu-ilmu Sosial, 2019)
This study aims to determine the implementation (DIKLAT) of Education and Training in improving work effectiveness in the Sibolga Sambas Sub-District Office by appealing the hioptesis that there is an influence (DIKLAT) of Education and Training on the work effectiveness of the Sibolga Sambas Sub-District Office. The research method used is descriptive causal comperative method . The author uses 21 respondents as a sample drawn from the entire population. The results showed a positive relationship between (DILLAT) Education and Training with work Effectiveness at the Sibolga Sambas Sub-District Office of 0.953, so that when interpreted on a scale the values ​​could be categorized rather low. Regression equation obtained Y = 3.673 + 0.883 X which shows the effect of Education and Training on work effectiveness. The t test showed that the hypothesis was accepted to be correct, where t count 13.639> 2.09302, which means that work effectiveness would increase by a regression coefficient / slop (0.883) if the variable (DIKLAT) education and training were added by one unit. While the coefficient of determination is known that education and training only contribute 90.7% to the effectiveness of work in the Sibolga Sambas District Office and the remaining 9.3% is influenced by other factors not examined.